2009
DOI: 10.1111/j.1532-950x.2009.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic and Histopathologic Evaluation of Extruded Canine Degenerate Disks

Abstract: The variability in cytologic findings and frequent presence of dysplastic spindloid cells suggest that cytology alone may not be a reliable tool to differentiate degenerate canine disk material from a mesenchymal neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
5
16
0
Order By: Relevance
“…These results are similar to the findings in two recent studies on the histopathological appearance of surgically removed IVD tissue where it was found that the histologic differences between the two dog types were minimal (Royal et al, 2009, Kranenburg et al, 2013. These results also correspond well with what was reported in another study of IVD degeneration in sagitally transected spines, where the histopathological appearances were largely similar in the two breed types (Bergknut et al, 2013a).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are similar to the findings in two recent studies on the histopathological appearance of surgically removed IVD tissue where it was found that the histologic differences between the two dog types were minimal (Royal et al, 2009, Kranenburg et al, 2013. These results also correspond well with what was reported in another study of IVD degeneration in sagitally transected spines, where the histopathological appearances were largely similar in the two breed types (Bergknut et al, 2013a).…”
Section: Discussionsupporting
confidence: 82%
“…no significant differences are seen between the two breed types in any of these individual parameters. The fact that only a few differences are seen between the two breed types in Thompson grade II and III is in accordance with a study by Royal et al on surgically removed degenerate disc material where it was found that the histologic differences between the two dog types was minimal (Royal et al, 2009). …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Also similar to dogs with thoracolumbar IVD extrusion, an inflammatory reaction was present in the cervical epidural space in 70% of affected dogs. This observation conflicts with another study in which only 27% of dogs had an inflammatory response .…”
Section: Discussionmentioning
confidence: 71%
“…It is unknown how much extruded disc material must be removed from the spinal canal to achieve successful outcomes in clinical patients. The inflammatory nature of extruded disc material has been demonstrated suggesting complete removal of disc material is warranted [11][12][13][14][15] . It is also unknown how much impact a surgical approach to the incorrect side has in the clinical patient.…”
Section: Chapter III Resultsmentioning
confidence: 99%